(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Background: This study was conducted in the Penipe canton, Chimborazo province, Ecuador, the Objetive: is the characterizing and classifying the local family agriculture production systems. Methodology: The researchers worked with a total of 1,055 families, from which they extracted a sample (n=68) to conduct a study on geographical location, zoning, and survey interview, which included technical, socioeconomic, productive, and environmental aspects of the farms from a quantitative and qualitative standpoint. Results: express the characteristics of the production systems, allowing classifying and classifying the production systems of family agriculture in the canton. The conglomerated analysis using Ward’s method and a 900-meter Euclidian distance divided the farms into three groups. Implications: Several aspects to be improved were identified, which limit the development of farms to be considered as sustainable systems, evaluating aspects of productivity, reliability in the productive system, resilience, adaptability, equity, and self-management by local producers. Conclusions: Specialized Family Agriculture (SFA) is made up of 19 families, with an average age of 54 years, land ownership of 1.57 hectares, additional labor hired at a rate of two days per week, and monthly earnings of 584 USD. Diversified Family Agriculture (DFF), composed of 34 families, with an average age of 53 years, land ownership of 6,99 ha, (95%) of families contracting additional labor to carry out agricultural activities, (8 daily wages/ campaign) and monthly earnings of 792 USD. Subsistence Family Agriculture (SFA), composed of 15 families, with an average age of 48 years, and land ownership of 0.54 ha, this production system is distinguished by the fact that it does not hire additional labor to carry out agricultural activities, as the majority of its output is devoted to self-sufficiency and earnings of 115 USD per month.